ANALISIS PENGENDALIAN KUALITAS PRODUK KARDUS MENGGUNAKAN METODE SIX SIGMA DI CV. AGZ - Mohammad Fachrurrozi Adi; Akhmad Wasiur Rizqi; Deny Andesta (LPPM Politeknik LP3I Medan, 2022)
Quality control is an activity that is used by companies to monitor and evaluate production activities and ensure that production activities meet production process standards. The purpose of this study is to help companies find out the causes of defects and create suggestions for improvement using the six sigma method. The six sigma method is one of the tools used to control quality. By using several stages, namely define, measure, analyze, improvement, control. From data processing and analysis, the total production is 160,800 pcs and the number of defects is 4303 pcs. Based on the results of the calculation of DPMO found as many as 80,280 per one million productions. Based on the Pareto diagram, the percentage of the most dominant types of defects is the type of paint defects that are not neat, so quality improvements are focused on these types of defects using fishbone diagrams.